QUALITY-DRIVEN DECISION-MAKING BY MAIN CONTRACTORS FOR THE MRT2 ELEVATED PROJECT - Md Zin, Nurulhayati; Zainol, Nurul Nadiah; Ahmad Zawawi, Emma Marinie (Journal of Civil Engineering, Science and Technology, 2025)
This paper explores the factors that influence quality-driven decision-making by main contractors. The construction industry, especially in large-scale projects like the MRT2 Elevated Project, faces challenges in maintaining high quality standards while managing time and cost pressures. These scenarios often lead to delays, cost overruns, and quality issues which may affect the overall success of a project. Despite the importance of quality-driven decision-making, there is limited understanding of the key factors that influence these decisions among main contractors. Therefore, the objective is to identify the key factors that impact quality-related decisions in the MRT2 Elevated Project in Klang Valley. Effective decision-making in quality is crucial for balancing time, cost, and quality in construction projects, particularly in large-scale projects like the MRT2, where delays and quality issues are common. Existing research highlights several important factors that help ensure projects meet quality standards. Using a quantitative approach, this study identifies fifteen (15) critical factors influencing quality-driven decision-making. Data were collected and analyzed using the Relative Importance Indices (RII) to rank these factors. The results show that the most important factors for main contractors are decision-maker capability; balancing the time, cost, and quality; and safety and health compliance. The study highlights the need to strengthen decision-making to align with these factors. The findings are significant as they can lead to improved practices in quality assurance and quality control within the construction industry.